Rice-straw-derived hybrid TiO2–SiO2 structures with enhanced photocatalytic properties for removal of hazardous dye in aqueous solutions. (February 2016) - Choi, Chulmin; Hwang, Kyung-Jun; Kim, Young Jin; Kim, Gunwoo; Park, Ju-Young; Jin, Sungho
Abstract: Rice straw, an agricultural bioresource, is utilized as a biotemplate in order to synthesize a hybrid TiO2 –SiO2 structure, and the resulting products were used for removing hazardous methylene blue dye from aqueous solutions. Samples of the as-prepared hybrid TiO2 –SiO2 structure are characterized by thermal gravity analysis, field emission scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, nitrogen gas adsorption/desorption measurement, and UV/vis spectroscopy. The results obtained show that the hybrid TiO2 –SiO2 structure possesses both anatase and rutile phases, along with amorphous SiO2 . Its specific surface area is determined to be 141.1 m 2 /g, and its pore size to be 3.77 nm. Light harvesting within the visible-light range is found to be enhanced by the use of this hybrid TiO2 –SiO2 structure. Moreover, the photocatalytic activity and stability are also improved, as demonstrated by the degradation of methylene blue dye under UV irradiation. Graphical abstract: Highlights: Rice straw containing Si provided a biotemplate for the hybrid TiO2 –SiO2 structure. This structure has a specific surface area of 141.1 m 2 /g and pore size of 3.7 nm. Light harvesting in the visible spectrum is enhanced. The structure was used as a photocatalyst for methylene blue degradation. Adsorption and photocatalytic activity were considerably enhanced.